2018
DOI: 10.1523/jneurosci.0564-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Representations of Stimulus Features Are Amplified during Memory Retrieval and Flexibly Aligned with Top-Down Goals

Abstract: In studies of human episodic memory, the phenomenon of reactivation has traditionally been observed in regions of occipitotemporal cortex (OTC) involved in visual perception. However, reactivation also occurs in lateral parietal cortex (LPC), and recent evidence suggests that stimulus-specific reactivation may be stronger in LPC than in OTC. These observations raise important questions about the nature of memory representations in LPC and their relationship to representations in OTC. Here, we report two fMRI e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
117
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 57 publications
17
117
1
Order By: Relevance
“…Here, we confirm prior findings of reactivation by showing spatially precise retinotopic activation in multiple visual areas, as well as reduced SNR during memory. We also show clear evidence that perception and memory responses are most similar in higher level visual areas as proposed by Pearson et al (2015) and paralleling prior findings (Favila et al, 2018;Breedlove et al, 2018). However, we also found systematic differences that could not be explained by lower SNR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we confirm prior findings of reactivation by showing spatially precise retinotopic activation in multiple visual areas, as well as reduced SNR during memory. We also show clear evidence that perception and memory responses are most similar in higher level visual areas as proposed by Pearson et al (2015) and paralleling prior findings (Favila et al, 2018;Breedlove et al, 2018). However, we also found systematic differences that could not be explained by lower SNR.…”
Section: Discussionsupporting
confidence: 91%
“…Pylyshyn, 2002). More recently, memory researchers have favored decoding and pattern similarity approaches over univariate activation analyses to examine the content of retrieved memories (Polyn et al, 2005;Kuhl et al, 2011;Favila et al, 2018). While these approaches are powerful, they do not explicitly specify the form mnemonic activity should take, and many activation schemes can lead to successful decoding.…”
mentioning
confidence: 99%
“…Our findings of feature-specific encoding effects demonstrate that multimodal details of complex episodes can be decomposed in the brain, even when encoded simultaneously. The specific pattern of our results converges with univariate and multivariate decoding studies previously using these types of features, including color (Uncapher et al, 2006;Favila et al, 2018), sounds (Gottlieb et al, 2012), and scenes (Park and Chun, 2009;Morgan et al, 2011;Staresina et al, 2011) to study perception and encoding. We additionally showed that these visuo-perceptual neural correlates were only present early on in encoding, which is consistent with relatively earlier subsequent memory effects in ventral visual areas shown using intracranial EEG (Long and Kahana, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…The systems consolidation view (Winocur and Moscovitch 2011) purports that such transfer of episodic (from hippocampus to cortex) or working memory traces (from visual to parietal and frontal regions, see Xu 2017). Further evidence from studies scanning both encoding and retrieval blocks, and find that memory representations during retrieval may be found in separate regions from encoding (Xiao et al 2017;Favila et al 2018) also support this transfer-based view. Furthermore, regions coding for 2 nd -order similarity between brain and model similarity (i.e., our IRAF regressors) with values below a statistical threshold (and therefore not visible in the IRAF maps in Fig.…”
Section: Contributions Of Visual Representations To Subsequent Memorymentioning
confidence: 95%
“…The nature of visual representations has been examined in at least three different domains of cognitive neuroscience: vision, semantic cognition, and episodic memory. Vision researchers have examined the representations of visual properties Rajalingham et al 2018), semantic cognition researchers, the representations of semantic features and categories (Konkle and Oliva 2012;Clarke et al 2013;Martin et al 2018), and episodic memory researchers, the representations that are reactivated during episodic memory tests (Kuhl et al 2012;Favila et al 2018).…”
Section: Introductionmentioning
confidence: 99%